Fourth-generation wireless networks [ applications and innovations - Adibi, Sasan , 1970-; Mobasher, Amin , 1978-; Tofigh, Tom , 1955-; Gale Group (Hershey, Pennsylvania : Information Science Reference, 2010)
"This book presents a comprehensive collection of recent findings in access technologies useful in the architecture of wireless networks"-- Provided by publisher
section 1. Network architectures -- section 2. Radio access protocols -- section 3. Physical layer advances
Description based on print version record
Includes bibliographical references and index
Keywords: Cell phone systems -- Technological innovations; Mobile communication systems -- Technological innovations; Wireless communication systems -- Technological innovations